2014
DOI: 10.1186/1532-429x-16-44
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional autopsy and magnetic resonance imaging in determining the cause of sudden death in the young

Abstract: BackgroundSudden death in the young is a tragic complication of a number of medical diseases. There is limited data regarding the utility of post-mortem Magnetic Resonance (MR) imaging and Computer Tomography (CT) scanning in determining the cause of sudden death. This study sought to compare the accuracy of post-mortem cross-sectional imaging (MR and CT) with the conventional autopsy in determining the cause of sudden death in the young.MethodsConsecutive patients from 2010 to 2012 (aged 1–35 years) who had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…In addition to traditional autopsy, some reports have used whole-body computed tomography and magnetic resonance imaging to identify structural heart abnormalities such as ARVC and HCM. 26,27 However, these imaging modalities were not used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to traditional autopsy, some reports have used whole-body computed tomography and magnetic resonance imaging to identify structural heart abnormalities such as ARVC and HCM. 26,27 However, these imaging modalities were not used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive studies of combined PMCT, PMCTA, and biopsies have the greatest sensitivity for cause of death determinations compared to conventional autopsy . Research on imaging alternatives to conventional autopsy will focus on reducing the cost and time of imaging autopsies in hopes of increasing the rate of imaging autopsy …”
Section: Use Of Forensic Radiology and Imaging In Medicinementioning
confidence: 99%
“…Computer tomography (CT) and cardiac magnetic resonance (CMR) have become increasingly important in diagnostic pathways and have also been explored in the postmortem setting. 22,23 Of interest, Puranik et al reported that CMR was able to accurately diagnose ARVC, HCM, myocardial infarction/CAD, ruptured aortic aneurysm, pulmonary embolus and myocarditis as the cause of death in 12 out of 12 subjects who went on to have confirmatory autopsy. 23 There were particular limitations noted such as the potential to overdiagnose conditions such as HCM due to myocardial edema or death during systole which artificially increase the ventricular septal thickness or ARVC whereby right ventricular dilatation is used as a diagnostic criteria, but the systolic dysfunction and regional dyskinesis diagnostic components are not met.…”
Section: Emerging Role Of Imagingmentioning
confidence: 99%
“…22,23 Of interest, Puranik et al reported that CMR was able to accurately diagnose ARVC, HCM, myocardial infarction/CAD, ruptured aortic aneurysm, pulmonary embolus and myocarditis as the cause of death in 12 out of 12 subjects who went on to have confirmatory autopsy. 23 There were particular limitations noted such as the potential to overdiagnose conditions such as HCM due to myocardial edema or death during systole which artificially increase the ventricular septal thickness or ARVC whereby right ventricular dilatation is used as a diagnostic criteria, but the systolic dysfunction and regional dyskinesis diagnostic components are not met. Of relevance, a recent study utilizing CMR in the diagnostic work up of out of hospital cardiac arrest patients showed that CMR performed within 7 days of presentation identified a diagnosis in all 44 patients, but more importantly was able to reclassify 11 out of the 26 cases without obstructive coronary disease after initial assessment with coronary angiography and echocardiography.…”
Section: Emerging Role Of Imagingmentioning
confidence: 99%